Operative otorhinolaryngology (Cambridge, Massachusetts, 1997)
This book completes with major specialist texts in Otoneurosurgery, Skull-Base Surgery, Head and Neck Surgery, Endoscopic Sinus Surgery or Facial Plastic Surgery
Keywords: otolaryngology, operative,otorhinolaryngologic diseases - surgery